การจัดการความรู้ของบุคลากรในโรงเรียนสาธิต - ศิลานุกิจ, ชนมณี (Ph.D. in Social Sciences Journal, 2017)
การจัดการความรู้ เป็นกระบวนการจัดการความรู้เพื่อสร้างคุณค่าให้เกิดขึ้น เป็นเทคนิค และหัวใจสำคัญที่บุคลากรพึงรู้จักและทำความเข้าใจให้ชัดเจนเพื่อให้สามารถจัดการได้อย่างเหมาะสมยังประโยชน์ให้เกิดแก่ตน องค์กรและสังคม โดยเฉพาะบุคลากรที่ปฏิบัติหน้าที่เกี่ยวกับการศึกษา บุคลาการที่ปฏิบัติหน้าที่ในโรงเรียนสาธิตอันอยู่ภายใต้การกำกับดูแลของมหาวิทยาลัยจึงมีภารกิจสำคัญ 4 ด้าน เช่นเดียวกับอาจารย์ในระดับอุดมศึกษา คือปฏิบัติหน้าที่ (1) การสอน (2) การวิจัย (3) การบริหารวิชาการ และ (4) การส่งเสริมศิลปวัฒนธรรมของไทย ดังนั้น การจัดการความรู้ของบุคลาการในโรงเรียนสาธิตจึงมีความสำคัญ อันประกอบด้วยกระบวนการจัดการความรู้ 6 ขั้นตอน คือ (1) การกำหนดหัวข้อความรู้ (2) การแสวงหาความรู้ (3) การแลกเปลี่ยนเรียนรู้ (4) การนำความรู้ไปใช้ (5) การจัดเก็บสะสมความรู้ และ (6) การประเมินผล ความรู้นั้นเป็นสิ่งที่มีไม่จำกัด ยิ่งใช้มากเท่าใด ยิ่งเพิ่มเติมความรู้และคุณค่าแห่งตนมากขึ้นเท่านั้น สิ่งสำคัญเหนือกกว่าการมีความรู้ คือ ความสามารถในการนำความรู้เหล่านั้น มาวิเคราะห์ สังเคราะห์ให้เป็น สร้างสรรค์ให้เป็นความรู้ที่สามารถนำมาใช้ประโยชน์ทั้งในและนอกโรงเรียนสาธิตอย่างเหมาะสม รวมถึงเกิดการสร้างนวัตกรรมการเรียนการสอนอย่างต่อเนื่องจนกลายเป็นวงจรที่เพิ่มพูนประสิทธิภาพของบุคลากรในโรงเรียนสาธิตและกลายเป็นวงจรแห่งการเรียนรู้ เพื่อพัฒนาคุณภาพการเรียนการสอนที่มีศักยภาพส่งผลต่อการสร้างอนาคตของชาติต่อไป KNOWLEDGE MANAGEMENT OF STAFF IN DEMONSTRATION SCHOOL Knowledge Management is the knowledge management process for create the value. Knowledge Management is also be the technique and the important core that the staffs have to know and understand about the meaning for choose the suitable process to get the personal, organization and social benefit. Especially for the personal benefit of education staffs in demonstration school that under the university control have 4 important duties as same as the lecturer in the university including (1) teaching (2) researching (3) education administration and (4) Thai cultural supporting. That’s mean the knowledge management of staff in demonstration school is important issue. There are 6 processes of knowledge management of staff in demonstration school as following; (1) Knowledge topic setting up, (2) Knowledge searching, (3) Knowledge sharing, (4) Knowledge using, (5) Knowledge collection and (6) Knowledge evaluation. The knowledge is unlimited thing, that’s mean will increase when use and improve the skill and value of each person. The most important of knowledge is how to bring the knowledge to the analysis process to be the creative knowledge that can be used for all people and only in the demonstration school but also outside. After that we can create the continuously learning innovation and transform our social to be the effective knowledge cycle of the staff in demonstration school.